Pengaruh Profitabilitas, Komite Audit, dan Kepemilikan Asing terhadap Kebijakan Dividen (Studi pada Perusahaan Properti Real Estate dan Kontruksi Bangunan yang Terdaftar di Bursa Efek) - Siahaan, Sri Devi (CV. Kalimasada Group, 2024)
This research aims to analyze the influence of profitability, audit committee and foreign ownership on dividend policy in property, real estate and building construction companies listed on the Indonesia Stock Exchange. By using secondary data from the company's annual financial reports for the 2018-2022 period and multiple regression analysis methods, the research results show that profitability and foreign ownership have a positive and significant influence on dividend policy, while the audit committee has no significant influence. Profitability as measured by Return on Assets (ROA) and foreign ownership are proven to increase the dividend payout ratio, while the presence of an audit committee does not show a significant impact. These results provide implications for company management and investors in understanding the factors that influence dividend policy, especially in the context of companies in Indonesia.